2020
DOI: 10.1111/cmi.13239
|View full text |Cite
|
Sign up to set email alerts
|

Three proline rotamases involved in calcium homeostasis play differential roles in stress tolerance, virulence and calcineurin regulation of Beauveria bassiana

Abstract: FK506‐sensitive proline rotamases (FPRs), also known as FK506‐binding proteins (FKBPs), can mediate immunosuppressive drug resistance in budding yeast but their physiological roles in filamentous fungi remain opaque. Here, we report that three FPRs (cytosolic/nuclear 12.15‐kD Fpr1, membrane‐associated 14.78‐kD Fpr2 and nuclear 50.43‐kD Fpr3) are all equally essential for cellular Ca2+ homeostasis and contribute significantly to calcineurin activity at different levels in the insect‐pathogenic fungus Beauveria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…However, many studies have indicated that Ca 2+ can participate in the stress response as a messenger in the process of an organism responding to various stresses including HS, and Ca 2+ -related signaling plays an important role in stress resistance as well as physiological and metabolic aspects of organisms (Liu et al 2018c ). Therefore, by using qRT-PCR, the expression of the most typical key proteins of the calcium signaling pathway such as calmodulin (CaM), calcineurin (CaN), and calcineurin-responsive zinc finger transcription factor (Crzl) in stress response was analyzed; the gene of prolyl cis–trans isomerase ( PPIase ) was also detected by qRT-PCR, since its product may interact with calcium-regulated phosphatases and may also be involved in the process of microbial response to HS (Mouhoumed et al 2020 ). Moreover, the expression of PQ biosynthesis-related genes ( PKS , Mon , Omef , Hydro , and FAD ) was detected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, many studies have indicated that Ca 2+ can participate in the stress response as a messenger in the process of an organism responding to various stresses including HS, and Ca 2+ -related signaling plays an important role in stress resistance as well as physiological and metabolic aspects of organisms (Liu et al 2018c ). Therefore, by using qRT-PCR, the expression of the most typical key proteins of the calcium signaling pathway such as calmodulin (CaM), calcineurin (CaN), and calcineurin-responsive zinc finger transcription factor (Crzl) in stress response was analyzed; the gene of prolyl cis–trans isomerase ( PPIase ) was also detected by qRT-PCR, since its product may interact with calcium-regulated phosphatases and may also be involved in the process of microbial response to HS (Mouhoumed et al 2020 ). Moreover, the expression of PQ biosynthesis-related genes ( PKS , Mon , Omef , Hydro , and FAD ) was detected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The metal ions in A. flavus were assayed by staining with the Ca 2+ -specific fluorescence dye Fura-2-AM (Fura-2 acetoxymethyl ester, 40702ES50, Yeasen, Shanghai, China), Na + -specific fluorescence dye SBFI-AM (sodium-binding benzofuran isophthalate acetoxymethyl ester, GC44876, GLPBIO, Montclair, CA, USA) and K + -specific fluorescence dye PBFI-AM (potassium-binding benzofuran isophthalate acetoxymethyl ester, GC18477, GLPBIO, Montclair, CA, USA) as previous reports [ 36–39 ]. All A. flavus strains were cultured in YES media, then collected and washed three times with PBS buffer to remove the media.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, cellular metal ions (Ca 2+ , Na + and K + ) in the WT, ∆fab1 and ∆fab1::fab1 strains were assessed by using specific fluorescent indicator dyes, including Ca 2+ -specific fluorescent probe Fura-2-AM (Fura-2 acetoxymethyl ester), Na + -specific fluorescent probe SBFI-AM (sodium-binding benzofuran isophthalate acetoxymethyl ester) and K + -specific fluorescent probe PBFI-AM (potassium-binding benzofuran isophthalate acetoxymethyl ester), according to previously described methods [36][37][38][39] .…”
Section: Deletion Of Fab1 Impacts Cellular Acidification and Metal Iomentioning
confidence: 99%
“…The types and levels of gene expression of pathogenic fungi vary greatly under the induction of secretions such as insect body wall, hemolymph or plant root. Under a high-temperature (32 • C) or hyperosmotic environment (0.5-M NaCl) or insect body wall culture, the expression of the BCNA of the A subunit encoding gene CaN in B. bassiana was significantly increased by calcinulinase, and the expression level varied with the induction time [8]. Other studies have shown that the MaSte12 gene of Metarhizium anisoplidae affects conidial germination but does not affect fungal sporulation or conidial stress resistance.…”
Section: Introductionmentioning
confidence: 99%